Pemberdayaan UMKM melalui Integrasi Digital Marketing dan Sistem Pembayaran Digital (QRIS dan Agen BNI 46) di Kecamatan Cipayung Kota Depok - Arimani, Corie; Fatahillah, Rosadi; Wulandari, Estha; Pratama, Tiara; Holiawati, Holiawati (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aims to empower MSMEs in Cipayung District, Depok City through the integration of digital marketing and digital payment systems based on QRIS and BNI 46 Agents. The problems faced by MSME actors include limited use of social media for marketing, low use of digital transactions, and minimal technical assistance. Activity methods include seminars, tutorials, direct practice, and online assistance. The results showed that 90% of participants succeeded in creating social media business accounts, 85% registered for QRIS, and 65% understood the function of BNI 46 Agents. The main obstacles were limited digital devices, content consistency, and the need for digital security materials. These results are in line with research by Hakim et al. (2023) and Fitriani Lestari (2024) on the importance of digital transformation of MSMEs. Rahmawati et al. (2025) also emphasized that digital system integration and ongoing support are effective strategies in empowering MSMEs as a whole.